Fatal occupational injuries in Taiwan, 1994–2005. Issue 4 (9th October 2009) - Ho, Shu-Chen; Wang, Li-Yu; Ho, Chi-Kung; Yang, Chun-Yuh
Abstract : Objectives: This study examines the trends in rates of fatal occupational injuries in Taiwan by demographic group and occupation for 1994–2005. Methods: Data on deaths due to injuries at work from 1994 through 2005 were obtained from the Department of Health which is responsible for the death registration system in Taiwan. Employment data, which were used as the denominators of fatality rates in this study, were retrieved from the Directorate-General of Budget and Accounting Statistics 'Employment and Earnings' database. A Poisson regression model was used to examine the trends in rates of fatal occupational injuries in various occupations while controlling for demographic characteristics. Results: Overall fatal occupational injury rates declined during the study period among all demographic groups and occupations. Adjusted annual changes in rates of fatal injuries ranged from a decrease of 13.6% a year in machine operators/related workers to a decrease of 35.9% in clerks. The annual decrement was faster for males than for females and for older workers compared to young workers. Conclusions: Despite declining rates, the number of fatal occupational injuries in Taiwan remains significant because of the growing work force. Future research should focus on the disparities in fatal injury trends.